Integrated nutrient management for sustaining wetland rice (Oryza sativa) production in mid hills altitude of Meghalaya - PANWAR, A S (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted, during rainy season of 2007 and 2008 at the research farm of ICAR Research Complex for NEH Region, Umiam, Meghalaya, to study the effect of organic and inorganic sources of nutrients in wetland rice. The results of two years study reveals that the growth parameters were improved with application of 5 tonnes/ha FYM + Azolla dual cropping + 75 per cent of the recommended dose of NPK (80:60:40 kg/ha, RDF). While higher yield attributes were recorded with 50% of the recommended dose of fertilizer in the presence of FYM 5 tonnes/ha + Azolla dual cropping resulted into maximum grain yield of 39.34 q/ha, which was 13.89% and 16.87% higher over alone application of recommended dose of NPK and bio-organics, respectively. Application of FYM 5 tonnes/ha + Azolla + Azospirillum found to produce grain yield equal with FYM 10 tonnes/ha and application of recommended dose of NPK without any bio-organic. The use of Azospirillum was promising in improving growth and yield of rice. The grain yield of rice recorded with FYM 5 tonnes/ha + seedling inoculation with Azospirillum in the presence of 75% recommended dose of NPK (38.34 q/ha) was significantly higher over that of 50% RDF with same bio-organics, but when Azolla dual cropping in place of Azospirillum was adopted, the maximum grain yield was recorded with 50% RDF, which was however, at par with that of 75 and 100% RDF applied together with same bio-organics, indicated that the use of biofertilizer can save 25-50 per cent of the recommended dose of NPK, besides substantial improvement in grain yield of wetland rice. The uptake of K was more than N and P. Maximum N and P uptake was recorded with FYM 5 tonnes/ha + Azolla dual cropping + 75 RDF, while maximum K uptake was recorded with the same bio-organics applied in the presence of 100 RDF. Highest net return with benefit : cost ratio was found with FYM 5 tonnes/ha + Azolla dual cropping + 50 RDF.